Single parents competing in a dual-earner society: Leveling the playing field - Rense Nieuwenhuis (Luxembourg Income Study (LIS), 2022)
This study set out to understand the poverty risks of single parents in the context of the rise of the dual-earner household. Data from the LIS database were used to analyze individuals and households from 18 OECD countries in the period 1984 to 2010. There were to main findings. The first is that single parents face higher relative income poverty risks (AROP) in the context of a large share of dual-earner households. This is related to the fact that the rise of dual earners is linked to a higher standard of living in society and therefore a higher poverty threshold that fewer single parents can reach based on a single income. Secondly, this overall pattern varied across institutional contexts: a rise of dual-earner households put single parents at a disadvantage only in the context of low public expenditure on ECEC, and of a lower degree of income replacement policies. Implications for theory and policy are discussed.
Keywords: 330; Alleinerziehende; Haushaltseinkommen; Armut; OECD-Staaten